Validation of porcine DNA analysis method for food products using selected primer and exogenous internal positive control in real-time PCR - Heryani; Nurjanah, Siti; Faridah, Didah Nur (Halal Studies and Society, 2024)
The method for porcine DNA analysis using real-time PCR is widely applied in the halal certification process and post-market monitoring. Therefore, this research aimed to validate porcine DNA analysis method using selected primer and exogenous internal positive control (IPC) as an alternative. The experiment was conducted in various stages, namely primer selection, sample extraction, efficiency testing, and method validation. The results of efficiency tests showed that using IPC at half concentration (Exo IPC Mix 5X and Exo IPC DNA 25X) provided reliable amplification with a Ct value of 27.57 ± 0.28 and RFU of 205.5 ± 14.85. The maximum DNA concentration that could be amplified without inhibition was 100 ng/µl. Validation tests showed specificity, sensitivity, linearity, PCR efficiency, and robustness. Among 23 positive and 23 negative samples, two positive samples (porcine collagen and collagen peptide) produced false negatives, while three negative samples had false positives after Ct 42.26. The method achieved a limit of detection (LOD) of 0.01 ng/l at Ct 33.29 ± 0.92, with linearity (r² = 0.996) and PCR efficiency (ϵ = 96.32). The results showed robustness to variations in master mix type, primer concentration, and annealing temperature, as well as resistance to inhibitors such as alginate, cellulose, EDTA, calcium ions, collagen peptide, and polysaccharides at 1 g/l. The performance of this method was also compared to the SNI ISO/TS 20224-3:2020 standard, showing potential as a viable alternative for porcine DNA testing. Moreover, further comparative research were recommended to fully establish the efficacy against national standards.